Особливості взаємодії громадянського суспільства та поліції в умовах тоталітарного політичного режиму - Субота, С. І.; Subota, S. I. (Право і безпека. - 2016. - № 1 (60). - С. 73–79, 2016)
На прикладі УРСР З’ясовано, що в умовах тоталітарного режиму всі громадські формування (добровільні народні дружини, товариства сприяння міліції, бригади сприяння міліції), які взаємодіяли з міліцією, по-перше, забезпечували існування й функціонування радянської влади в будь-яких її проявах і формах, по-друге, їх діяльність забезпечувала боротьбу зі справжніми та «уявними» ворогами радянської влади. Доведено, що взаємодія громадських формувань з міліцією в УРСР носила односторонній характер. Громадські формування цього типу проводили й виражали волю держави, а не суспільства, до їх функцій не входив контроль за діяльністю правоохоронної системи взагалі та міліції зокрема.

It is noted that features of interaction between police and civil society to some extent are due to a type of state (political) regime. On the example of Soviet Ukraine it is established that all public organizations within totalitarian regime (voluntary people’s guards, associations assisting police, brigades of police assistance) that interacted with the police, were formed at the initiative of the state and to perform its tasks. The population interacted with the representatives of police, following marginal and ideological motives. Public organizations that actively interacted with the police, consisted mainly of party and Komsomol activists, workers and members of the administrative sections of the local, village, town and district councils. In this regard, they actually, first of all, ensured the existence and functioning of Soviet power in all its forms, and secondly, their activities ensured the fighting against real and «imaginary» enemies of Soviet power. It is proved that the interaction of social groups with the police in the time of Ukrainian SSR was one-sided. Civil organizations of this type carried out and expressed the will of the state, but not of the society; their functions did not include control over the activities of law enforcement system in general and the police in particular.

На примере УССР определено, что в условиях тоталитарного режима все гражданские формирования (добровольные народные дружины, общества содействия милиции, бригады содействия милиции), которые взаимодействовали с милицией, во-первых, обеспечивали существование и функционирование советской власти в любых её проявлениях и формах, вовторых, их деятельность обеспечивала борьбу с настоящими и «вымышленными» врагами советской власти. Доказано, что взаимодействие гражданских формирований с милицией в УССР носило односторонний характер. Гражданские формирования такого типа проводили и выражали волю государства, а не общества, в их функции не входил контроль за деятельностью правоохранительной системы в целом и милиции в частности.
Features of interaction between civil society and the police within totalitarian political regime
Особенности взаимодействия гражданского общества и полиции в условиях тоталитарного режима
Субота, С. І. Особливості взаємодії громадянського суспільства та поліції в умовах тоталітарного політичного режиму / С. І. Субота // Право і безпека. - 2016. - № 1 (60). - С. 73–79.
Subota, S.I. (2016), “Features of interaction between civil society and the police within totalitarian political regime” [“Osoblyvosti vzaiemodii hromadianskoho suspilstva ta politsii v umovakh totalitarnoho politychnoho rezhymu”], Pravo i Bezpeka, No. 1, pp. 73–79.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; громадянське суспільство; правоохоронні органи; поліція; політичний режим; тоталітарний режим; УРСР; civil society; law enforcement agencies; police; political regime; totalitarian regime; УССР; Ukrainian SSR; Історія. History. История; гражданское общество; правоохранительные органы; полиция; политический режим; тоталитарный режим